Cardiac Restricted Overexpression of Kinase-dead Mammalian Target of Rapamycin (mTOR) Mutant Impairs the mTOR-mediated Signaling and Cardiac Function - Shen, Wei-Hua (American Society for Biochemistry and Molecular Biology, 2008)
Mammalian target of rapamycin (mTOR) is a key regulator for cell growth through modulating components of the translation machinery. Previously, numerous pharmacological studies using rapamycin suggested that mTOR has an important role in regulating cardiac hypertrophic growth. To further investigate this assumption, we have generated two lines of cardiac specific mTOR transgenic mice, kinase-dead (kd) mTOR and constitutively active (ca) mTOR, using α-myosin heavy chain promoter. α-Myosin heavy chain (αMHC)-mTOR(kd) mice had a near complete inhibition of p70 S6k and 4E-BP1 phosphorylation, whereas αMHC-mTOR(ca) had a significant increase in p70 S6k and 4E-BP1 phosphorylation. Although the cardiac function of αMHC-mTOR(kd) mice was significantly altered, the cardiac morphology of these transgenic mice was normal. The cardiac hypertrophic growth in response to physiological and pathological stimuli was not different in αMHC-mTOR(kd) and αMHC-mTOR(ca) transgenic mice when compared with that of nontransgenic littermates. These findings suggest that the mTOR-mediated signaling pathway is not essential to cardiac hypertrophic growth but is involved in regulating cardiac function. Additional analysis of cardiac responses to fasting-refeeding or acute insulin administration indicated that αMHC-mTOR(kd) mice had a largely impaired physiological response to nutrient energy supply and insulin stimulation.